2019
DOI: 10.1128/aem.02453-18
|View full text |Cite
|
Sign up to set email alerts
|

The MarR Family Regulator BmrR Is Involved in Bile Tolerance of Bifidobacterium longum BBMN68 via Controlling the Expression of an ABC Transporter

Abstract: In order to colonize the human gastrointestinal tract and exert their beneficial effects, bifidobacteria must effectively cope with toxic bile salts in the intestine; however, the molecular mechanism underlying bile tolerance is poorly understood. In this study, heterologous expression of a MarR family transcriptional regulator, BmrR, significantly reduced the ox bile resistance ofLactococcus lactisNZ9000, suggesting that BmrR might play a role in the bile stress response.In silicoanalysis combined with revers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…At the same time, they may activate membrane-associated efflux pumps able to extrude bile salts and bile acids accumulated in the cytoplasm. Specifically, several multidrug transporters belonging to the ATP-binding cassette or the major facilitator superfamily have been identified as mediators of bile tolerance in B. breve and B. longum strains [70] , [92] , [93] . However, other defence mechanisms may be exploited by bifidobacterial taxa to limit the harmful effects of bile, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, they may activate membrane-associated efflux pumps able to extrude bile salts and bile acids accumulated in the cytoplasm. Specifically, several multidrug transporters belonging to the ATP-binding cassette or the major facilitator superfamily have been identified as mediators of bile tolerance in B. breve and B. longum strains [70] , [92] , [93] . However, other defence mechanisms may be exploited by bifidobacterial taxa to limit the harmful effects of bile, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…ABC transporters are divided into several groups with different characteristics associated with the uptake of nutrients and export of drugs (Locher 2016). ABC transporter BmrAB, comprising of 652-and 671-amino acid proteins, is required for bile acid tolerance in Bifidobacterium longum BBMN68 (Xu et al 2019). The amino acid sequence of BmrA (652 aa, BBMN68_1797) in B. longum is similar to the ABC transporter ATP-binding protein AMUC_RS00905 (34% identity; 54% similarity, 594 aa).…”
mentioning
confidence: 99%
“…In B. longum BBMN68, another bile-induced MDR transporter system was described recently (231). The transport system was found to be encoded within a polycistronic operon that consists of three genes, encoding the heterodimeric ABC transporter BmrAB and the MarR-family transcriptional regulator BmrR (231). In silico structural analysis and DNA-binding analysis of BmrR indicated that the expression of the bmrRAB operon is autoregulated by BmrR, which functions as a repressor.…”
Section: Molecular Mechanisms Of Bile Stress Responsementioning
confidence: 99%
“…In silico structural analysis and DNA-binding analysis of BmrR indicated that the expression of the bmrRAB operon is autoregulated by BmrR, which functions as a repressor. Under nonstress conditions, BmrR is assumed to bind to an inverted repeat sequence (ATTGTTG-N 6 -CAACAAT) in the promoter region of the operon, while being released from the promoter when some component of the bile interacts with BmrR and causes conformational changes in the DNA binding site (231). Heterologous overexpression of the bmrA gene and bmrB gene of B. longum BBMN68 in L. lactis significantly increased the host's resistance to ox bile (231).…”
Section: Molecular Mechanisms Of Bile Stress Responsementioning
confidence: 99%
See 1 more Smart Citation